Factors Affecting Employee Work Productivity in Khairunnas Foundation Bengkulu City - Ita Lestari; Sri Handayani; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the factors that affect employee’s productivity at Khairunnas Foundation in Bengkulu City. The type of research used was survey research. The subject of this research is Khairunnas Foundation of Bengkulu City, while the objects in the study are the factors that affect employee’s productivity. The data collection method used was a questionnaire. The data analysis technique used was multiple linear regression analysis method using validity test analysis, reliability test, partial test (t), simultaneous test (F) and analysis of the coefficient of determination using the help of the SPSS program for windows22. The number of samples were 33 respondents. The results of this study are: a). from three factors that affect employee’s productivity, there is a significant correlation between training and employee’s productivity at Khairunnas Foundation in Bengkulu City. A significant correlation between training and employee’s productivity, the more training, the better the employees are in carrying out their work. It can be seen that the significance value is 0.051> 0.05 and t count> t table (t count = 2.038)> (t table = 1.697). b). There is a significant relationship between education, training and motivation on employee’s productivity at Khairunnas Foundation in Bengkulu City. This can be seen at the significance level of 0.043 <0.05 and f count> f table (f count = 3.079)> (f table = 2.92).